The fever code ebook - Dashner, James (Maze Runner, 2016)
THE #1 NEW YORK TIMES BESTSELLING MAZE RUNNER SERIES • “[A] mysterious survival saga that passionate fans describe as a fusion of Lord of the Flies [and] The Hunger Games ” ( Entertainment Weekly ) The story that fans all over the world have been waiting for — the story of how Thomas and WICKED built the Maze — is finally here. You do not want to miss it. Once there was a world’s end. The forests burned, the lakes and rivers dried up, and the oceans swelled. Then came a plague, and fever spread across the globe. Families died, violence reigned, and man killed man. Next came WICKED, who were looking for an answer. And then they found the perfect boy. The boy’s name was Thomas, and Thomas built a maze. Now there are secrets. There are lies. And there are loyalties history could never have foreseen. This is the story of that boy, Thomas, and how he built a maze that only he could tear down. All will be revealed. A prequel to the worldwide Maze Runner phenomenon, The Fever Code is the book that holds all the answers. How did WICKED find the Gladers? Who are Group B? And what side are Thomas and Teresa really on? Lies will be exposed. Secrets will be uncovered. Loyalties will be proven. Fans will never see the truth coming. Before there was the Maze, there was The Fever Code . Look for more books in the blockbuster Maze Runner series: THE MAZE RUNNER • THE SCORCH TRIALS • THE DEATH CURE • THE KILL ORDER • THE FEVER CODE